The Role of Astrocytes in CNS Inflammation - Giovannoni, Federico; Quintana, Francisco J. (Trends in immunology, 2020)
Astrocytes are the most abundant cell type in the central nervous system (CNS), performing complex functions in health and disease. It is now clear that multiple astrocyte subsets or activation states (plastic phenotypes driven by intrinsic and extrinsic cues) can be identified, associated to specific genomic programs and functions. The characterization of these subsets and the mechanisms that control them may provide unique insights into the pathogenesis of neurologic diseases, and identify potential targets for therapeutic intervention. In this article, we provide an overview of the role of astrocytes in CNS inflammation, highlighting recent discoveries on astrocyte subsets and the mechanisms that control them. Astrocytes display functional and phenotypic heterogeneity across and within CNS regions under homeostatic conditions.CNS insults (trauma, infection, autoimmune inflammation, protein aggregates) induce a broad array of astrocyte activation states, poorly defined in terms of phenotype, function, and role in human pathology.Astrocyte activation during acute microbial infection is essential for pathogen clearance but can contribute to long-term neurological impairments.The plasticity of astrocytes and their ability to adopt either a proinflammatory or an anti-inflammatory phenotype could be targeted for therapeutic intervention.